Redundancy among risk predictors derived from heart rate variability and dynamics: ALLSTAR big data analysis. Issue 1 (17th August 2020) - Yuda, Emi; Ueda, Norihiro; Kisohara, Masaya; Hayano, Junichiro
Abstract : Background: Many indices of heart rate variability (HRV) and heart rate dynamics have been proposed as cardiovascular mortality risk predictors, but the redundancy between their predictive powers is unknown. Methods: From the Allostatic State Mapping by Ambulatory ECG Repository project database, 24‐hr ECG data showing continuous sinus rhythm were extracted and SD of normal‐to‐normal R‐R interval (SDNN), very‐low‐frequency power (VLF), scaling exponent α1, deceleration capacity (DC), and non‐Gaussianity λ25s were calculated. The values were dichotomized into high‐risk and low‐risk values using the cutoffs reported in previous studies to predict mortality after acute myocardial infarction. The rate of multiple high‐risk predictors accumulating in the same person was examined and was compared with the rate expected under the assumption that these predictors are independent of each other. Results: Among 265, 291 ECG data from the ALLSTAR database, the rates of subjects with high‐risk SDNN, DC, VLF, α1, and λ25s values were 2.95, 2.75, 5.89, 15.75, and 18.82%, respectively. The observed rate of subjects without any high‐risk value was 66.68%, which was 1.10 times the expected rate (60.74%). The ratios of observed rate to the expected rate at which one, two, three, four, and five high‐risk values accumulate in the same person were 0.73 times (24.10 and 32.82%), 1.10 times (6.56 and 5.99%), 4.26 times (1.87 and 0.44%), 47.66 times (0.63 and 0.013%), and 1, 140.66 times (0.16 and 0.00014%), respectively. Conclusions: High‐risk predictors of HRV and heart rate dynamics tend to cluster in the same person, indicating a high degree of redundancy between them.